KEANEKARAGAMAN MAKROZOBENTOS DI SUNGAI SUMBER NGENEP KECAMATAN KARANGPLOSO KABUPATEN MALANG - Fitriyah Fitriyah; Arum Sekar Ayu Kinanti (Prodi Biologi Universitas PGRI Ronggolawe, 2024)
Rivers are a water source that has many roles in people's lives and is inhabited by many organisms. The quality of water can be seen from the number of organisms that live in that water. Organisms that can be used as biological indicators are macrozoobenthos. Macrozoobenthos are organisms whose movement characteristics tend to be limited and where they live permanently. The way to find indications of pollution in a river is to calculate the diversity of macrozoobenthos populations in the riverbed. The purpose of this study was to determine the diversity of macrozoobenthos in the Sumber Ngenep River, Karangploso District, Malang Regency. This research is quantitative research with an exploratory method. Sampling was carried out at 3 stations with 3 repetitions at each station. Identification using 3 literature and data analysis using the Shannon-Wiener Diversity Index (H') and Simpson Dominance Index (D). The research results obtained 10 macrozoobenthos genera. The diversity index value of station 1 (1.389), station 2 (1.638), station 3 (1.343). Dominance index value of station 1 (0.286), station 2 (0.262), station 3 (0.309).